2016
DOI: 10.3390/nu8110711
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels Are Higher in Whole Compared to Skim Human Milk, Supporting a Cellular Contribution

Abstract: Human milk (HM) contains a plethora of metabolic hormones, including leptin, which is thought to participate in the regulation of the appetite of the developing infant. Leptin in HM is derived from a combination of de novo mammary synthesis and transfer from the maternal serum. Moreover, leptin is partially lipophilic and is also present in HM cells. However, leptin has predominately been measured in skim HM, which contains neither fat nor cells. We optimised an enzyme-linked immunosorbent assay for leptin mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Interestingly, longitudinal changes observed in concentrations of skim milk leptin in this study were not confirmed in whole HM. Caution in the interpretation of leptin concentrations measured in skim HM should be exercised, as whole milk measures are more indicative of the level of hormone consumed by the infant [28]. The consistent concentrations of adiponectin and leptin in whole HM over the first 12 months of life may be indicative of a continuing roles of appetite programming, priming neural connections involved in the appetite circuitry, thereby contributing to long-lasting enhanced appetite control and BC of breastfed infants throughout life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, longitudinal changes observed in concentrations of skim milk leptin in this study were not confirmed in whole HM. Caution in the interpretation of leptin concentrations measured in skim HM should be exercised, as whole milk measures are more indicative of the level of hormone consumed by the infant [28]. The consistent concentrations of adiponectin and leptin in whole HM over the first 12 months of life may be indicative of a continuing roles of appetite programming, priming neural connections involved in the appetite circuitry, thereby contributing to long-lasting enhanced appetite control and BC of breastfed infants throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin concentrations in whole and skim HM were measured using the DuoSet Human Leptin enzyme-linked immunosorbent assay (ELISA) (R&D Systems, Minneapolis, MN, USA) as described previously [28]. The detection limit was 0.05 ng/mL with a recovery of 96.3% ± 1.2% ( n = 10) for skim milk and 97.1% ± 9.1% ( n = 10) for whole milk leptin and an inter-assay coefficient of variation (CV) of <7.2%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models (rat, mouse), injection of leptin into the fourth ventricle has been shown to delay GE [ 30 ] and oral administration reduced food intake [ 31 ]. Leptin in HM is by far the most studied appetite hormone, but predominantly in skim milk [ 32 ]. Leptin measured in skim HM was not associated with time between feeds [ 33 , 34 ] or GE [ 34 ] in term breastfed infants, emphasizing the need for studies including whole milk leptin, where the levels of leptin are shown to be higher [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin in HM is by far the most studied appetite hormone, but predominantly in skim milk [ 32 ]. Leptin measured in skim HM was not associated with time between feeds [ 33 , 34 ] or GE [ 34 ] in term breastfed infants, emphasizing the need for studies including whole milk leptin, where the levels of leptin are shown to be higher [ 32 ]. Adiponectin has the highest concentration of any appetite hormone in HM.…”
Section: Introductionmentioning
confidence: 99%